2018
DOI: 10.3390/v10030132
|View full text |Cite
|
Sign up to set email alerts
|

High Mobility Group Box 1 Influences HSV1716 Spread and Acts as an Adjuvant to Chemotherapy

Abstract: High Mobility Group Box 1 (HMGB1) is a multifunctional protein that plays various roles in the processes of inflammation, cancer, and other diseases. Many reports document abundant HMGB1 release following infection with oncolytic viruses (OVs). Further, other groups including previous reports from our laboratory highlight the synergistic effects of OVs with chemotherapy drugs. Here, we show that virus-free supernatants have varying cytotoxic potential, and HMGB1 is actively secreted by two established fibrobla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 61 publications
0
18
0
Order By: Relevance
“…The control (SCR, scramble) shRNA used the target sequence 5′-CCTAAGGTTAAGTCGCCCTCG-3′, as previously described 33 . Lentiviral production protocols have been previously described 34 . Briefly, lentivirus was produced by transfecting HEK293T cells with a cocktail containing psPAX2 (a gift from Didier Trono, Addgene plasmid #12260), pCMV-vesicular stomatitis virus G (VSV-G; a gift from Bob Weinberg, Addgene plasmid #8454), and p.LKO1 (Addgene plasmid #24150) modified to express either the STING knockdown or control shRNA.…”
Section: Methodsmentioning
confidence: 99%
“…The control (SCR, scramble) shRNA used the target sequence 5′-CCTAAGGTTAAGTCGCCCTCG-3′, as previously described 33 . Lentiviral production protocols have been previously described 34 . Briefly, lentivirus was produced by transfecting HEK293T cells with a cocktail containing psPAX2 (a gift from Didier Trono, Addgene plasmid #12260), pCMV-vesicular stomatitis virus G (VSV-G; a gift from Bob Weinberg, Addgene plasmid #8454), and p.LKO1 (Addgene plasmid #24150) modified to express either the STING knockdown or control shRNA.…”
Section: Methodsmentioning
confidence: 99%
“…Cell viability was assessed by using a Trypan blue exclusion test, as described by Fiorito et al [32,33], with modifications. In brief, either A549 or MDBK cells were seeded into flat 24-well plates and incubated overnight.…”
Section: Cell Viability Assaymentioning
confidence: 99%
“…While HMGB1 release has been observed upon infection of murine fibroblasts, 16 no significant release was noted upon HSV-1 infection of human and mouse breast cancer cells after infection with HSV-1 in vitro 17, 18. To evaluate if HMGB1 is released after virotherapy of brain tumors, we infected primary patient derived GBM neurospheres and glioma cell lines and measured HMGB1 level released in the conditioned medium by ELISA after infection (Figures 1A and 1B).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, it has also been shown to have a direct and potent anti-herpetic effect on cultured cells in vitro and has been associated with increased survival of mice with encephalitis 35, 36, 37. Contrary to the well-documented anti-viral effects of glycyrrhizin, a more recent study showed that direct incubation of mouse fibroblasts with glycyrrhizin led to a small increase in infected GFP-positive cells, with modest effects on oHSV-mediated cell toxicity, suggesting that there might be HMGB1-independent effects of glycyrrhizin on mouse fibroblast cultures 16 . Here, we utilized HMGB1-blocking antibodies to understand the impact of HMGB1 on the tumor micro-environment after virotherapy.…”
Section: Discussionmentioning
confidence: 99%